Greater fuel efficiency is potentially preferable to reducing NO x emissions for aviation’s climate impacts - Agnieszka Skowron (Nature Portfolio, 2021)
The regulation of aircraft engine NO x emissions was introduced to improve local air quality and reduce NO x emissions at altitude. Here, the authors find that greater fuel efficiency of aircrafts, and therefore lower CO2 emissions, could be preferable to reducing NO x emissions in terms of the aviation industries future climate impacts.